2009
DOI: 10.1080/13576500802680336
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical facial expressions in portraits and hemispheric laterality: A literature review

Abstract: Studies of facial asymmetry have revealed that the left and the right sides of the face differ in emotional attributes. This paper reviews many of these distinctions to determine how these asymmetries influence portrait paintings. It does so by relating research involving emotional expression to aesthetic pleasantness in portraits. For example, facial expressions are often asymmetrical-the left side of the face is more emotionally expressive and more often connotes negative emotions than the right side. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 78 publications
8
38
1
Order By: Relevance
“…Finally, in art, portraits are slightly more frequent with left than right three-quarter views (McManus & Humphrey, 1973). Although there may be different explanations to this phenomenon, like ease of drawing (see Powell & Schirillo, 2009), this can reinforce the perceptual experience hypothesis.…”
supporting
confidence: 58%
“…Finally, in art, portraits are slightly more frequent with left than right three-quarter views (McManus & Humphrey, 1973). Although there may be different explanations to this phenomenon, like ease of drawing (see Powell & Schirillo, 2009), this can reinforce the perceptual experience hypothesis.…”
supporting
confidence: 58%
“…Also, ASD children spent significantly less time on the right eye than both TD groups. Previous research has reported an asymmetry in facial expression that the right side of the face (from the observer's view) is more emotionally expressive than the left side (from the observer's view), reflecting a right cerebral hemispheric superiority in the production of emotional expressions (see Powell & Schirillo, 2009, for a review). Our findings of the left eye bias (from the observer's view) in children with ASD suggest that they may avoid fixating on the more emotionally expressive side of the face.…”
Section: Discussionmentioning
confidence: 98%
“…Portraits featuring the left face are judged as more emotional [25] and the leftward posing bias also appears to be stronger among females [24]. The preference for turning the left cheek in portraits appears to be the result of right hemisphere activation [22][25].…”
Section: Introductionmentioning
confidence: 99%